Comparison of Multivariate Discrimination Techniques for Clinical Data— Application to the Thyroid Functional State - Coomans, D.; Broeckaert, I.; Jonckheer, M.; Massart, D. L. (Methods of Information in Medicine, 1983)
In this paper sixteen discrimination techniques are compared on the basis of a data base concerning the thyroid function. Five laboratory tests are available for 215 patients divided into three diagnostic classes, i. e. euthyroidism, hypothyroidism and hyperthyroidism. For all techniques correct classification rates were determined using the leave-one-out procedure. Moreover, for the probabilistic techniques, the quality of the obtained probabilities was evaluated. It has been shown that most of the techniques perform well. However, the probabilistic techniques are to be preferred.
Keywords: Discriminant Analysis; Pattern Recognition; Thyroid Function; Performance Criteria; Bayes-ian Classification